2021
DOI: 10.3390/molecules26040921
|View full text |Cite
|
Sign up to set email alerts
|

Raman Microspectroscopic Investigation and Classification of Breast Cancer Pathological Characteristics

Abstract: Breast cancer is one of the major cancers of women in the world. Despite significant progress in its treatment, an early diagnosis can effectively reduce its incidence rate and mortality. To improve the reliability of Raman-based tumor detection and analysis methods, we conducted an ex vivo study to unveil the compositional features of healthy control (HC), solid papillary carcinoma (SPC), mucinous carcinoma (MC), ductal carcinoma in situ (DCIS), and invasive ductal carcinoma (IDC) tissue samples. Following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The tissue spectrum arises from the CH 2 lipid stretch present in mammalian tissue. 25 Importantly, in tumours that did not have any nanotags added, and used as controls, the characteristic peaks of the PPY were not present (Fig. S5 †), indicating that the peaks from the SESORS measurements were in fact those from the PPY, and hence nanotags.…”
Section: †)mentioning
confidence: 99%
“…The tissue spectrum arises from the CH 2 lipid stretch present in mammalian tissue. 25 Importantly, in tumours that did not have any nanotags added, and used as controls, the characteristic peaks of the PPY were not present (Fig. S5 †), indicating that the peaks from the SESORS measurements were in fact those from the PPY, and hence nanotags.…”
Section: †)mentioning
confidence: 99%
“…Li et al found a decrease in lipids and suggested that tumors share a common phenotype of uncontrolled cell proliferation and, therefore, they consume large amounts of lipids. 53 However, more recent studies have found a specific type of increase in lipids in breast tumor tissues: the unsaturated fatty acid. In 2016, Sixian You et al observed an increase of polyunsaturated fatty acids in the human breast cancer tissues.…”
Section: Machine Learning Models and Biomolecular Predictionsmentioning
confidence: 99%
“…Remarkably, among vibrational spectroscopies, Raman offers structural information for various moieties and, as an imaging technique, can reach the submicron scale without causing tissue damage or cell death for a typical image acquisition time. This technique has been used recently in many investigations in living cells, for instance, in breast cancer pathology at the aim of classification and diagnosis (Li et al, 2021;Cutshaw et al, 2023), of bacterial infections at the single-cell level (Lima et al, 2022), visualization and quantification of neurodegenerative protein aggregates (Sun and Chen, 2020), as well as imaging of lipid droplets content in prostate cell models (Hislop et al, 2022). We have previously shown that a strategy combining Raman spectroscopy along with multivariate analysis allows identifying at least four intracellular regions, following their chemical modifications upon treatment with metallodrugs in single living cells (Mamián-López et al, 2021).…”
Section: Introductionmentioning
confidence: 99%